Concise Synthesis of Tetrazole–Ketopiperazines by Two Consecutive Ugi Reactions. Issue 1 (17th November 2014) - Zarganes‐Tzitzikas, Tryfon; Patil, Pravin; Khoury, Kareem; Herdtweck, Eberhardt; Dömling, Alexander
Abstract: A concise route for the synthesis of the novel compound class tetrazole–diketopiperazines was developed. The approach involves the use of two multicomponent reactions: the Ugi tetrazole four‐component reaction (4CR) and the classical intramolecular Ugi 4CR. The tetrazole–diketopiperazines comprise analogs of and are bioisosteric to bioactive diketopiperazines, which thus draws attention for novel bioactive compound design. This scaffold was produced to fill the screening deck of the European lead factory. Abstract : A novel compound class of tetrazole–diketopiperazines is described. Two multicomponent reactions are used during the synthesis: the Ugi tetrazole four‐component reaction (4CR) and the classical intramolecular Ugi 4CR. Tetrazole–diketopiperazines comprise analogs of and are bioisosteric to bioactive diketopiperazines. The scaffold is currently produced to fill the screening deck of the European Lead Factory.